Patent management : protecting intellectual property and innovation - Gassmann, Oliver, 1967-; Bader, Martin A.; Thompson, Mark James (Management for professionals, 2021)
This book provides an overview of the common concepts and building blocks of patent management. It addresses executives in the areas of innovation, R & D, patent and intellectual property management as well as academics and students. The authors give valuable information on the characteristics of patent and intellectual property management, based on the collaboration with companies and organizations from Europe, China, Japan, Argentina, Brazil, India, Canada and the US. A reference for managers who want to bring information technology innovation with a clear intellectual property strategy to the market. A very readable book. Thomas Landolt, Managing Director, IBM A really comprehensive, all-in book about Patents - strategy, value, management and commercialization. And not forgetting what they are for - foster innovation. Dr. Joerg Thomaier, Head of IP Bayer Group.